Combined transcriptomic and proteomic analysis reveals the response mechanisms of alfalfa to freezing stress - Ren, NaiPeng; Liu, JieLin; Wang, HongBao; Liu, ZhaoMing; Liu, XiangPing; Li, GuoLiang (Frontiers in Plant Science, 2026)
IntroductionAlfalfa (Medicago sativa L.) is the most important perennial forage crop cultivated globally. However, extreme environmental conditions, such as freezing stress, can significantly impact alfalfa’s growth and development. The potential mechanisms through which alfalfa responds to freezing stress remain largely unexplored.MethodsIn this study, we analyzed the physiological indices, transcriptomes and proteomes of the cold-tolerant alfalfa cultivar “Dongnong NO.1” and the cold-sensitive cultivar “Bara 218TR” at -5°C.ResultsThe results indicated that the levels of antioxidant enzyme and osmoregulatory substances in “Dongnong NO.1” were significantly higher than in “Bara 218TR”. Additionally, the levels of malondialdehyde (MDA) and relative electrolyte leakage (REL) were found be lower in “Dongnong NO.1” than in “Bara 218TR”. Further transcriptomic analysis revealed that the differentially expressed genes (DEGs) found in both alfalfa cultivars were predominantly enriched in the AP2/ERF-ERF transcription factor family and in multiple signaling pathways. Weighted gene co-expression network analysis (WGCNA) revealed that the physiological processes associated with freezing stress tolerance in the two alfalfa cultivars are closely linked to DEGs that regulate protein synthesis, calcium signaling, the inhibition of iron toxicity, and the reduction of cell wall stiffness. Proteomics analysis indicates that differentially abundant proteins (DAPs) respond to frost damage by maintaining protein stability, antioxidant defense, and metabolic regulation. Integrated transcriptomic and proteomic analyses indicate that pathways related to carbohydrate metabolism, biotic stress defense, cell wall modification, and phenylpropanoid biosynthesis are key to alfalfa’s response to frost damage.DiscussionThis study improves our understanding of the molecular mechanisms underlying alfalfa’s freezing resistance and provides insights for the further screening and in-depth investigation of candidate genes with potential functions against freezing stress.